Respostas
respondido por:
2
c) ![\dfrac{x}{a} - \dfrac{x}{b} = \dfrac{2}{a} \dfrac{x}{a} - \dfrac{x}{b} = \dfrac{2}{a}](https://tex.z-dn.net/?f=+%5Cdfrac%7Bx%7D%7Ba%7D+-+%5Cdfrac%7Bx%7D%7Bb%7D+%3D+%5Cdfrac%7B2%7D%7Ba%7D+)
![x.( \dfrac{1}{a} - \dfrac{1}{b}) = \dfrac{2}{a} x.( \dfrac{1}{a} - \dfrac{1}{b}) = \dfrac{2}{a}](https://tex.z-dn.net/?f=x.%28+%5Cdfrac%7B1%7D%7Ba%7D+-+%5Cdfrac%7B1%7D%7Bb%7D%29+%3D+%5Cdfrac%7B2%7D%7Ba%7D+)
![x.( \dfrac{b-a}{ab}) = \dfrac{2}{a} x.( \dfrac{b-a}{ab}) = \dfrac{2}{a}](https://tex.z-dn.net/?f=x.%28+%5Cdfrac%7Bb-a%7D%7Bab%7D%29+%3D+%5Cdfrac%7B2%7D%7Ba%7D+)
![x.( \dfrac{b-a}{b}) = \dfrac{2}{1} x.( \dfrac{b-a}{b}) = \dfrac{2}{1}](https://tex.z-dn.net/?f=x.%28+%5Cdfrac%7Bb-a%7D%7Bb%7D%29+%3D+%5Cdfrac%7B2%7D%7B1%7D+)
![x = \dfrac{2}{\frac{b-a}{b}} x = \dfrac{2}{\frac{b-a}{b}}](https://tex.z-dn.net/?f=x+%3D+%5Cdfrac%7B2%7D%7B%5Cfrac%7Bb-a%7D%7Bb%7D%7D+)
![x = 2.\dfrac{b}{b-a}} x = 2.\dfrac{b}{b-a}}](https://tex.z-dn.net/?f=x+%3D+2.%5Cdfrac%7Bb%7D%7Bb-a%7D%7D+)
![x = \dfrac{2b}{b-a}} x = \dfrac{2b}{b-a}}](https://tex.z-dn.net/?f=x+%3D+%5Cdfrac%7B2b%7D%7Bb-a%7D%7D+)
d)![3a(x-2)=2b(x+1) 3a(x-2)=2b(x+1)](https://tex.z-dn.net/?f=3a%28x-2%29%3D2b%28x%2B1%29)
![3ax-6a=2bx+2b 3ax-6a=2bx+2b](https://tex.z-dn.net/?f=3ax-6a%3D2bx%2B2b)
![3ax-2bx=6a+2b 3ax-2bx=6a+2b](https://tex.z-dn.net/?f=3ax-2bx%3D6a%2B2b)
![(3a-2b)x=6a+2b (3a-2b)x=6a+2b](https://tex.z-dn.net/?f=%283a-2b%29x%3D6a%2B2b)
![x= \dfrac{6a+2b}{3a-2b} x= \dfrac{6a+2b}{3a-2b}](https://tex.z-dn.net/?f=x%3D+%5Cdfrac%7B6a%2B2b%7D%7B3a-2b%7D+)
d)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás